Human Dignity: the Foundation of Human Rights and Religious Freedom (Memoria y Civilización, 2016)
The concept of human dignity lies at the heart of many national and international conventions of human rights. This idea, based on man's rationality, can be found already in Greco-Roman Antiquity, was fully developed in Christianity, in its synthesis with the Biblical conception of man as image of God. With the secularization of the European mind from the 18th century onwards, the justification of human dignity becomes problematic. This most influential attempt to justify it by secular rationality came from Kant, who saw man’s dignity as deriving from his capacity for moral reasoning and from it came the notions of autonomy and equality. However, during the last two centuries, secularized cultures produced skeptical attitudes toward both the Judeo-Christian and Kantian concepts of the intrinsic dignity of man, which eventually paved the way for twentieth-century totalitarian-isms. After the horrors of Nazism, concerns about putting human rights in the centre of culture, politics and law compelled a search ”•largely impossible”• for a common idea of human dignity, shared by different philosophical traditions, both religious and secular. During the years after World War II, especially after the Second Vatican Council, there was a renewed discovery of human rights as based on human dignity by Catholicism, which, in view of the different reduc-tionist or destructive tendencies found in the secularized culture, perhaps is the most satisfactory approach. Finally, the problem of religious freedom is examined as a case study for further reflections on human dignity.